BEYOND DICHOTOMIES: SOETANDYO WIGNJOSOEBROTO’S VISION FOR A MODERATED LEGAL PARADIGM - Nalle, Victor Imanuel W. (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract This article employs a legal biography approach to review the thoughts of Indonesian legal philosopher Soetandyo Wignjosoebroto regarding the complexity and distinctiveness of this field of study, as well as the importance of moderating it. Soetandyo portrays law as a system that must maintain its complexity as it reflects the intricate nature of reality. In an increasingly pluralistic and intricate societal context, identifying applicable laws becomes a challenging task. Consequently, Soetandyo underscores the significance of interconnecting legal science with other disciplines. In terms of decolonization of law, Soetandyo’s perspective, which avoids dichotomizing Western law from indigenous legal systems, assumes paramount importance. He alerts us to the peril of falling into the myth of the Western vs. Eastern dichotomy within the realm of legal science. Such a line of thought could impede our legal system’s ability to adapt to universal values. Taken as a whole, Soetandyo’s thoughts illustrate the necessity of tempering the study of law by perceiving it as an open system unbound by rigid methodologies. He also highlights the need for a robust epistemological foundation and a moderate approach when addressing complex issues such as the decolonization of law and the integration of legal studies with the social sciences. Abstrak Artikel ini menggunakan pendekatan biografi hukum untuk mengulas pemikiran filosof hukum Indonesia, Soetandyo Wignjosoebroto, tentang ilmu hukum yang menekankan kompleksitas dan kekhasan ilmu ini serta pentingnya memoderasinya. Pemikiran Soetandyo menunjukkan hukum sebagai sistem yang harus mempertahankan kompleksitasnya karena merefleksikan realitas yang kompleks. Dalam masyarakat yang semakin plural dan kompleks, identifikasi hukum yang berlaku menjadi tugas yang rumit. Oleh karena itu, Soetandyo menekankan pentingnya menghubungkan ilmu hukum dengan disiplin ilmu lain. Dalam konteks dekolonisasi hukum, pandangan Soetandyo yang menghindari pemisahan antara hukum Barat dan hukum lokal menjadi signifikan. Dia mengingatkan tentang bahaya jatuh ke dalam mitos dikotomi Barat dan Timur dalam ilmu hukum. Pemikiran semacam itu bisa membuat sistem hukum kita gagal beradaptasi dengan nilai-nilai universal. Secara keseluruhan, pemikiran Soetandyo mengilustrasikan kebutuhan untuk memoderasi ilmu hukum denganmelihatnya sebagai sistem terbuka yang tidak terikat pada satu metode tertentu. Ia juga menyoroti pentingnya landasan epistemologi yang kuat dan pendekatan moderat dalam menghadapi isu-isu kompleks seperti dekolonisasi hukum dan integrasi dengan ilmu sosial.